Ultrasonic characterization of emulsions: milk and water in oil - Higuti, R. T. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
Measurements of ultrasonic attenuation and velocity in milk and low concentration water-in-oil (W/O) emulsion were conducted, using a measurement cell with a double-element transducer that eliminates diffraction losses. The milk is characterized by the attenuation coefficient, while in the case of water-in-oil emulsions, the characterization is best represented by the propagation velocity.
Keywords: Attenuation; Emulsions; Thermal effects; Thermodynamic properties; Ultrasonic diffraction; Ultrasonic propagation; Ultrasonic transducers; Ultrasonic velocity; Attenuation coefficient; Diffraction losses; Propagation velocity; Ultrasonic attenuation; Water in oil emulsion; Ultrasonic measurement